Sistem Minimum Berbasis Mikrokontroler ATmega2560 sebagai Sistem Pengaman pada Analogi Lemari Penyimpanan Brankas - Muchammad Takdir Sholehati; Arief Goeritno (Jurnal Rekayasa Elektrika, 2018)
A minimum system based on ATmega2560 microcontroller has been created that functioned as a safety system in the analogy of the cupboard for storage of the safes. Making the minimum system is done through a number of phases, namely integrating the system, programming against the microcontroller system, and validation test in the form of system performance measurement through giving the forced state. System integration is in the form of installing a device on two lines in the input port and two lines in the output port of the microcontroller. Programming is based on algorithms and the syntax of Arduino IDE-based through 6 (six) stages, namely pins configuration, variable and constants declaration, initialization, main program, retrieved and send data, and output. The validation test is carried out in the form of 4 (four) conditions, namely a) when the RFID module is not detected, b) when the card is detected by the RFID module, c) when the door is opened, and the buzzer is "on", the card is not detected when tagged on the antenna, and d) when the door is forcibly opened, and the buzzer is "on", while the card is detected when tagged on the antenna. Maximizing the security against the door of analogy the cupboard for storage of the safes is detected by the limit switch condition when the door is opened forcefully and the buzzer sounds. For neutralizing conditions for buzzer conditions, it is done through tagging an RFID card through the antenna. The buzzer still sounds, if the blank data is unreadable by the RFID module, while the buzzer can be neutralized if the card was tagged, the data card stored is read by the RFID module.